2008
DOI: 10.1128/mcb.00201-08
|View full text |Cite
|
Sign up to set email alerts
|

mGluR-Dependent Long-Term Depression Is Associated with Increased Phosphorylation of S6 and Synthesis of Elongation Factor 1A but Remains Expressed in S6K-Deficient Mice

Abstract: Metabotropic glutamate receptor-dependent long-term depression (mGluR-LTD) in the hippocampus requires rapid protein synthesis, which suggests that mGluR activation is coupled to signaling pathways that regulate translation. Herein, we have investigated the signaling pathways that couple group I mGluRs to ribosomal S6 protein phosphorylation and 5oligopyrimidine tract (5TOP)-encoded protein synthesis during mGluR-LTD. We found that mGluR-LTD was associated with increased phosphorylation of p70S6 kinase (S6K1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 53 publications
(81 reference statements)
4
104
2
1
Order By: Relevance
“…Previous studies have reported increases in 35S-methionine incorporation (Kelleher et al 2004b), induced expression of 5TOP mRNAs (Tsokas 2005;Tsokas et al 2007;Gobert et al 2008), and increases in protein synthesis (Kelleher et al 2004b;Klann and Dever 2004;Antion et al 2008a) after LTP induction. One possible explanation is that mechanisms of perforant path LTP are different than forms of LTP studies in hippocampal slices in vitro.…”
Section: Robust Phosphorylation Of Rps6 Is Not Accompanied By Increasmentioning
confidence: 93%
“…Previous studies have reported increases in 35S-methionine incorporation (Kelleher et al 2004b), induced expression of 5TOP mRNAs (Tsokas 2005;Tsokas et al 2007;Gobert et al 2008), and increases in protein synthesis (Kelleher et al 2004b;Klann and Dever 2004;Antion et al 2008a) after LTP induction. One possible explanation is that mechanisms of perforant path LTP are different than forms of LTP studies in hippocampal slices in vitro.…”
Section: Robust Phosphorylation Of Rps6 Is Not Accompanied By Increasmentioning
confidence: 93%
“…In contrast, in Aplysia neurons, S6K, but not 4E-BP, appears to be the major effector of mTORC1 for long-term facilitation (44). In mammals, S6K appears to be involved mainly in the regulation of long-lasting decreases in synaptic strength because metabotropic glutamate receptor-induced LTD is enhanced in slices from S6K2 Ϫ/Ϫ mice (but not in those from S6K1 Ϫ/Ϫ mice) (42). Lack of S6K1 leads to a variety of complex behavioral phenotypes, which include hypoactive behavior, impaired short-term fear memory, deficient conditioned taste aversion and spatial memory and decreased contextual fear memory 7 days (but not 1 day) after training, and reduced latent inhibition of conditioned taste aversion and normal spatial memory as determined by the Morris water maze (43).…”
Section: Mtor and Eif4f Complex In Synaptic Plasticity And Memorymentioning
confidence: 94%
“…Ϫ/Ϫ mice display impaired protein synthesis-independent E-LTP but normal protein synthesis-dependent L-LTP (42,43), demonstrating that S6K does not control the translation of mRNAs that underlie L-LTP. In contrast, in Aplysia neurons, S6K, but not 4E-BP, appears to be the major effector of mTORC1 for long-term facilitation (44).…”
Section: Mtor and Eif4f Complex In Synaptic Plasticity And Memorymentioning
confidence: 99%
“…There are at least two signaling pathways that link mGluR activation to the initiation of translation and LTD: activation of extracellular signal-regulated kinase (ERK) by mitogen-activated protein kinase kinase (MEK), and activation of mammalian target of rapamycin (mTOR) through phosphoinositide-3-kinase (PI3K) and Akt. Thus, (RS)-3,5-dihydrophenylglycine (DHPG) increases levels of phosphorylated ERK and mTOR (Choe and Wang, 2001a,b;Gallagher et al, 2004;Banko et al, 2006;Antion et al, 2008) and initiates translation through the phosphorylation and activation of eIF4E (Banko et al, 2006). Furthermore, mGluR activation increases other regulators of protein synthesis such as mRNA polyadenylation (Shin et al, 2004) and p70S6 kinase activity (Antion et al, 2008).…”
Section: Introductionmentioning
confidence: 99%